Assessment of salivary flow and anxiety in patients rehabilitated with implant-supported prostheses - Agda Marobo Andreotti; Marcelo Coelho Goiato; Mariana Vilela Sônego; Emily Vivianne Freitas da Silva; Daniela Micheline Dos Santos (Wolters Kluwer Medknow Publications, 2019)
Background: The aim of this study was to verify, through self-assessment questionnaires, the influence of implant-supported prosthesis in salivary flow and anxiety of patients rehabilitated with them. Materials and Methods: Visual analog scale (VAS) questionnaire about xerostomia and State-Trait Anxiety Inventory were applied before (T1) and after 2 days (T2) and 3 weeks (T3) of prostheses installation. The study included patients rehabilitated with implant-supported prostheses containing three or more dental elements. A total of 17 patients were evaluated. Results: In VAS questionnaire, there was a significant increase in the difficulty of speaking and swallowing with dry mouth. The other VAS questions showed no statistically significant difference, indicating no changes in patients' salivary flow. Conclusions: It was concluded that the installation of implant-supported prostheses does not lead to major changes in patients' perception about their salivary flow and psychological state, causing no improvement or worsening in the characteristics evaluated.